Strategy of the Nuclear, Biological, and Chemical Detachment in Responding to a Novel Disease Pandemic (A Case Study of Assistance Operations in Natuna in 2020) - Robert Eryanto Tumanggor; Sigit Purwanto; Sugiri (CV. Rayyan Dwi Bharata, 2026)
Novel disease pandemics have demonstrated that biological threats can significantly affect national stability, public health, and national resilience. Normatively, the Nuclear, Biological, and Chemical Engineering Detachment (Denzinubika), as the Chemical, Biological, Radiological, and Nuclear (CBRN) unit of the Indonesian Army, is expected to possess optimal capabilities in supporting Military Operations Other Than War (MOOTW) for pandemic response. However, the implementation of assistance operations is still influenced by various internal and external factors that affect the effectiveness of the unit’s mission. This study aims to analyze these factors and formulate strategies for enhancing Denzinubika’s capabilities in addressing future biological threats. This study employed a qualitative descriptive method, with data collected through interviews, document studies, and field observations. Data analysis was conducted using the Miles and Huberman model, consisting of data collection, data reduction, data display, and conclusion drawing. The analytical framework used in this study includes the Ends-Ways-Means Strategy Theory of Arthur F. Lykke Jr. (1989), Defense Theory of Barry Buzan (1991), Capacity Building Theory of Grindle (1997), and Military Readiness Theory of James J. Tritten (1994).The findings indicate that the factors influencing pandemic assistance operations include personnel competence, CBRN capabilities and equipment, organizational structure, operational experience, policy support, technological development, cross-sector cooperation, and the dynamics of biological threats. The required strategies include strengthening organizational capacity, improving personnel capabilities, modernizing CBRN facilities and infrastructure, and enhancing cooperation and interoperability. The study concludes that strengthening organizational capacity and integrated operational readiness are key factors in ensuring Denzinubika’s effectiveness in responding to novel disease pandemics.